2021
DOI: 10.1111/1750-3841.15686
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resin coating on the quality characteristics of chicken eggs during storage

Abstract: In this study, after washing, changes in the quality characteristics of chicken eggs coated with apricot, almond, and sour cherry tree resins were examined during two different temperatures (4 • C and 22 • C) storage for 60 days.While air cell height, weight loss, albumen and yolk pH and a* (redness) values increased in all samples during storage, Haugh unit, albumen and yolk index, shell fracture and vitelline membrane strength, albumen and yolk L* (lightness) and b* (yellowness) values decreased (P < 0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
1
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
5
8
1
2
Order By: Relevance
“…Eggs lose weight irrespective of the storage temperature. However, the rate of EWL in lowtemperature condition is lower than in high storage temperature (Akter et al, 2014). In present trial, EWL increased with storage length.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Eggs lose weight irrespective of the storage temperature. However, the rate of EWL in lowtemperature condition is lower than in high storage temperature (Akter et al, 2014). In present trial, EWL increased with storage length.…”
Section: Discussioncontrasting
confidence: 51%
“…In the same vein, there was no difference in egg shape index in this study. Previous studies show that egg shape index was not affected by storage length (Tilki & Saatci, 2004;Raji et al, 2009;Akter et al, 2014;Abioja et al, 2021). Shell percentage and thickness were not affected by the length of storage in this study.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Similar to the results obtained in the present study, Akarca et al . (2021) reported that air cell values increased in all egg samples during storage, whereas this increase was slower in sour cherry and almond resin‐coated ones. The eggs coated with some preserving agents might show positive effect of limiting the increase of air cell depth during storage (Drabik et al ., 2021).…”
Section: Resultsmentioning
confidence: 96%